2003
DOI: 10.1046/j.1600-6143.2003.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Renal Transplantation: Why Not?

Abstract: Dialysis has been the long-established initial choice of treatment for persons with end-stage renal disease. Transplantation before dialysis, or preemptive renal transplantation (PRT), has been controversial because of the paucity of clinical evidence that has clarified the benefits vs. risks of this approach. However, several recent observational analyses indicate that PRT is the optimal strategy to benefit patients requiring renal replacement therapy. This current review will discuss the advantages that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…Our findings seem to be better than those of other reports. 10,11,29 Because our study group is small, our finding about the effectiveness of pre-emptive kidney transplantation in patients with T1D and ESRD needs to be seen as preliminary. The challenge is how to increase frequency of pre-emptive kidney transplantation in patients with T1D and ESRD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our findings seem to be better than those of other reports. 10,11,29 Because our study group is small, our finding about the effectiveness of pre-emptive kidney transplantation in patients with T1D and ESRD needs to be seen as preliminary. The challenge is how to increase frequency of pre-emptive kidney transplantation in patients with T1D and ESRD.…”
Section: Discussionmentioning
confidence: 96%
“…The challenge is how to increase frequency of pre-emptive kidney transplantation in patients with T1D and ESRD. 11 In the Joslin cohort such transplantation was implemented in 20% of patients who developed ESRD in the 2000s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKT has beter outcomes for both post transplant graft and patient survival and also co-morbidities happening during a dialysis period (10,11). Mange et al showed improved graft survival of PKT in 8481 living donor transplantation with 52% decrease for graft loss for PKT over non preemptive (12). Kasiske et al found similar results for both living and deceased donor transplantation (13).…”
Section: Introductionmentioning
confidence: 93%
“…In 2005, 2.3% of incident ESRD patients underwent preemptive transplantation, whereas the remaining patients started dialysis treatment (2). The progression from advanced CKD to dialysis, rather than to preemptive transplantation, can be attributed to a number of system and physician barriers such as late nephrology referral, UNOS requirements that creatinine clearance be Ͻ20 ml/min before a patient may be placed on the deceased donor kidney transplantation wait list, time to complete the medical evaluation for transplantation, or lack of timely availability of a kidney, whether from a deceased or live kidney donor (8,(17)(18)(19)(20)(21). Uncertainty regarding the optimal level of impaired kidney function at which the transplant should be performed and the possibility that preemptive transplant patients' adherence to immunosuppressive medications might be reduced compared with those who experience the hardships of dialysis therapy before transplantation also concern nephrologists (10).…”
mentioning
confidence: 99%